Structures of Fluoro, Amino, and Thiol Inhibitors Bound to the [Fe4S4] Protein IspH1. Issue 7 (10th January 2013) - Span, Ingrid; Wang, Ke; Wang, Weixue; Jauch, Johann; Eisenreich, Wolfgang; Bacher, Adelbert; Oldfield, Eric; Groll, Michael
<x xml:space="preserve">Abstract</x> The iron–sulfur protein IspH catalyzes a key step in isoprenoid biosynthesis in bacteria and malaria parasites. Crystal structures of IspH complexed with three substrate analogues reveal their mode of binding and suggest new routes to inhibitor design.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>